2020
DOI: 10.3390/cancers12041031
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Protein VDAC1 at the Crossroads of Cancer Cell Metabolism: The Epigenetic Link

Abstract: Carcinogenesis is a complicated process that involves the deregulation of epigenetics, resulting in cellular transformational events, such as proliferation, differentiation, and metastasis. Most chromatin-modifying enzymes utilize metabolites as co-factors or substrates and thus are directly dependent on such metabolites as acetyl-coenzyme A, S-adenosylmethionine, and NAD+. Here, we show that using specific siRNA to deplete a tumor of VDAC1 not only led to reprograming of the cancer cell metabolism but also al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 122 publications
(207 reference statements)
2
33
0
Order By: Relevance
“…Therefore, mitochondria supplying these metabolites are involved in controlling chromatin modifications 4 . Since upon VDAC1 silencing, the mitochondrial metabolism is highly reduced, 16,17,67,68 it is expected that decreasing VDAC1 expression levels would alter epigenetic signaling, and thereby gene expression 23 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, mitochondria supplying these metabolites are involved in controlling chromatin modifications 4 . Since upon VDAC1 silencing, the mitochondrial metabolism is highly reduced, 16,17,67,68 it is expected that decreasing VDAC1 expression levels would alter epigenetic signaling, and thereby gene expression 23 …”
Section: Resultsmentioning
confidence: 99%
“…VDAC1 as the transporter providing substrates for chromatin modification is heavily implicated in epigenetic modifications and thereby in the regulation of nuclear function. Indeed, we recently demonstrated that metabolic rewiring seen after depleting VDAC1 in GBM tumors is a consequence of limiting the substrates for chromatin modification, thereby affecting the metabolism–epigenetic axis 23 …”
Section: Introductionmentioning
confidence: 99%
“…Finally, the possibility of targeting metabolic pathways and Ca 2+ dynamics to manipulate the epigenome is a fascinating idea. New findings are emerging (Arif et al, 2017;Lombardi et al, 2019;Amsalem et al, 2020), and it will now be critical to understand the mechanisms by which concerted alterations in metabolism and Ca 2+ signaling regulate epigenetic-mediated transcriptional control in cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have provided evidence for this link. Alteration of mitochondrial metabolism upon VDAC1 depletion in glioblastoma cells limits the production of essential metabolic mediators of epigenetic processes, such as NADH, citrate, and acetyl-CoA (Arif et al, 2017;Amsalem et al, 2020). The associated changes in histone acetylation and methylation have profound effects on tumor growth, suggesting that this intricate link between Ca 2+ , metabolism and epigenetics may be exploited as an innovative therapeutic strategy for glioblastoma and other cancers (Arif et al, 2017;Amsalem et al, 2020).…”
Section: Ca 2+ Entry In the Mitochondria And Regulation Of Mitochondrmentioning
confidence: 99%
“…The adipose tissue and adipose-derived cells are able to interact with CSCs and have been shown to promote fatty acid oxidation in CSCs and chemoresistance [ 201 ]. The mitochondria are also known to play a role in CSC chemoresistance [ 202 ]. This is unsurprising as the mitochondria are central to many cellular processes such as metabolism, signaling and apoptosis.…”
Section: Properties Of Cancer Stem Cellsmentioning
confidence: 99%